Practical Manual of Tricuspid Valve Diseases (Springer International Publishing, 2018)
This book provides a comprehensive overview of tricuspid valve disease and an overview of different therapeutic options such as surgical and percutaneous approaches, current clinical trials and registries in the field of tricuspid valve disease. The book has an educational goal with key messages highlighted at the end of each chapter to assist comprehension of the often complex concepts. Practical Manual of Tricuspid Valve Diseases assists the clinician in dealing with different manifestations of tricuspid valve disease and providing help for choosing the best option for the management of these patients. It therefore serves as the standard reference regarding all aspects of tricuspid valve disease in adults and will be of importance to all medical professionals involved in the management of these patients.